Factors Predicting Cognitive Function in Patients with Sleep-related Breathing Disorders - Roopngam, Thanchanok; Puwarawuttipanit, Wimolrat; Koositamongkol, Sarunya; Apiwattanasawee, Polporn (Nursing Science Journal of Thailand, 2020)
Purpose: To investigate the predictive power of the severity of sleep apnea/hypopnea, body mass index, serum albumin, and physical activity in cognitive function of patients with sleep-related breathing disorders. Design: Predictive research design. Methods: The sample consisted of 140 patients with sleep-related breathing disorders receiving services in Otolaryngology Department at Faculty of Medicine Vajira Hospital. The eligible subjects had to be 18 years and above and have ten points on Epworth Sleepiness Scale. Questionnaires used in the study were the demographic and health data record form, the Epworth Sleepiness -Thai version, Physical Activity Questionnaire, and Mini-Mental State Examination Thai 2002. Data were analyzed using descriptive statistics and multiple logistic regression. Main findings: Patients with sleep-related breathing disorders who had lower serum albumin levels have cognitive impairment (AOR = 11.87, 95%CI = 2.91, 48.35, p < .001). Patients with sleep-related breathing disorders who had insufficient physical activity also had cognitive impairment (AOR = 63.84, 95% CI = 16.76, 243.16, p < .001). In addition, both lower serum albumin and insufficient physical activity was able to predict cognitive impairment at 66.8 percent (Negelkerke R2 = .668). Conclusion and recommendations: The result showed the statistically significant prediction of lower serum albumin level and insufficient physical activity on cognitive impairment of patients with sleep-related breathing disorders. Therefore, nurses should monitor albumin level and advice the patients on intake of specific protein nutrients. Encourage age-appropriate physical activity to reduce cognitive impairment.